Effect of plant extraction (Hibiscus, black grain and Fenugreek) on growth and yield of bean (Viacia faba L.) - Issa, Falah Hasan; Abo Tlasha, Jaber Jassim; Herby, Huda Hussein (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted at Experimental researches Unit " ALL – Bender location" Department of Plant Production during 2016-2017 growing season. The experiment included studying the effect the foliar application of Plant extraction ( T1 control with distill water , T2 Fenugreek extraction 5g L-1 and T3 10g L-1 , T4 black grain extraction 5g L-1 and T5 10g L-1 , T6 Hibscus extraction 5g L-1 and T7 10g L-1 treatment on bean Vicia faba L. cv. Local . Randomized Completely Block Design (R.C.B.D) were used with three replicates. The means were compared according to L.S.D test at the level 0.05. The results showed the superiority of Hibscus extraction (10 g/ L) in plant height , leaf area , fresh and dry weight of vegetative growth , flowers setting % , number and weight of pods , fresh and dry weight of seeds per plant reached ( 43.58cm, 41.12Dcm2, 192.54g, 77.04g, 57.45%, 36.02pod, 534.43g, 280.78g and 104.08g) respectively, 5g.L-1 of Hibiscus extraction treatment was significantly creased the number of seeds reached130.32seeds.plant-1 .